FAITH TOURISM POTENTIAL OF KONYA IN TERMS OF CHRISTIAN SACRED SITES - Gamze Temizel; Melis Attar (European Scientific Journal, ESJ, 2015)
Among the countries In the Middle East, Turkey is the second country that has the most biblical sites after Israel. It is called as ―The Other Holy Land‖ because of this reason. The land of Turkey which is bounded by the Mediterranean, Aegean, and Black Seas is referred as Asia Minor or Anatolia in Biblical reference works. Asia Minor or Anatolia as mentioned in history or the present day Turkey is important for Christianity to understand the background of the New Testament. Approximately two-thirds of New Testament books were written either to or from churches in Turkey. The three major apostles; Peter, Paul, and John either ministered or lived in Turkey. Turkey‘s rich spiritual heritage starts at the very beginning in the book of Genesis. Konya or Iconium as mentioned in history is one of the important cities of Turkey in terms of its historical and cultural heritage. It‘s a city that has an important place both in Christian and Islamic world, even in history and present day. Although Konya is famous today because of its Muslim mosques, its theological schools and its connection with the great Sufi mystic Celaleddin Rumi; better known as Mevlana, the 13th century Sufi mystic, poet, philosopher and founder of the Mevlevi order of whirling dervishes, Konya has a biblical significance since it was mentioned in the New Testament as one of the cities visited by Apostle Paul. In the first years of Christianity, St. Paul visited the city in three of his missionary voyages. Iconium, Lystra and Derbe are some of the New Testament Sites in Konya. In this study it has been aimed to reveal the religious tourism potential of present Konya in terms of its biblical significance for the Christian world. In line with this purpose, the study starts with a brief history of Konya, continues with the biblical significance of the city and gives detailed information about Christian sacred sites (New Testament sites) in present Konya. In the end of the study, the religious tourism potential of Konya has been argued.